2013
DOI: 10.1080/17429145.2013.832424
|View full text |Cite
|
Sign up to set email alerts
|

Salicylic acid increases the defense reaction against bunt and smut pathogens in wheat calli

Abstract: The role of salicylic acid (SA) in regulating wheat calli growth and peroxidase activity in the co-culture with bunt (Tilletia caries (D.C.) Tul.) and smut (Ustilago tritici Pers.) pathogens was studied in this work. We found that the influence of SA increased the number of globular high-density sites with meristema-like cells and reduced the number of low-structured sites with parenchyma-like cells in wheat calli. SA inhibited fungi spores germination, mycelium growth, and formation of its new spores during t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…POX is one of the first enzymes responding and providing defence mechanism against plant–pathogens (Sulman et al., ). POXs are involved in the lignification, suberification, polymerization of hydroxy proline‐rich glycoproteins and resistance against pathogens in plants by acting as barriers against pathogen attack (Hammond‐Kosack & Jones, ; Maksimov, Troshina, Surina, & Cerepanova, and Yoshida, Kaothien, Matsui, Kawaoka, & Shinmyo, ). Our data are supported by the reports from other authors where they have demonstrated that the infection with the plant–pathogen could lead to enhanced POX activity in the host–plant tissue especially those showing field resistant as compared to the susceptible ones (Mydlarz & Harvell, ).…”
Section: Discussionmentioning
confidence: 99%
“…POX is one of the first enzymes responding and providing defence mechanism against plant–pathogens (Sulman et al., ). POXs are involved in the lignification, suberification, polymerization of hydroxy proline‐rich glycoproteins and resistance against pathogens in plants by acting as barriers against pathogen attack (Hammond‐Kosack & Jones, ; Maksimov, Troshina, Surina, & Cerepanova, and Yoshida, Kaothien, Matsui, Kawaoka, & Shinmyo, ). Our data are supported by the reports from other authors where they have demonstrated that the infection with the plant–pathogen could lead to enhanced POX activity in the host–plant tissue especially those showing field resistant as compared to the susceptible ones (Mydlarz & Harvell, ).…”
Section: Discussionmentioning
confidence: 99%
“…Peroxidase: Peroxidase (POX) is one of the first enzymes responding and providing fast defense against plant pathogens (Sulman et al, 2001). The POXs are involved in the lignification, suberification, polymerization of hydroxy-proline-rich glycoproteins, regulation of cell wall elongation, wound healing and resistance against pathogens in plants ( Hammond-Kosack and Jones, 1996;Yoshida et al, 2003;Maksimov et al, 2014). The POX activity was significantly higher in BBTV infected plants of both cultivars, as compared to healthy (Fig.…”
Section: Total Phenolmentioning
confidence: 96%
“…POXs are involved in the lignification, suberification, polymerization of hydroxy-proline-rich glycoproteins, regulation of cell wall elongation, wound healing, and resistance against pathogens in plants ( Hammond-Kosack & Jones 1996;Yoshida et al 2003;Maksimov et al 2014). POX activity was significantly higher in noninoculated plants of both susceptible genotypes, as compared to resistant genotypes ( Figure 1D).…”
Section: Peroxidase Activitymentioning
confidence: 98%